Natural shear wave propagation speed is influenced by both changes in myocardial structural properties as well as loading conditions. (8th February 2021) - Bezy, S; Duchenne, J; Orlowska, M; Amoni, M; Caenen, A; Keijzer, LBH; Mccutcheon, K; Ingelaere, S; Cvijic, M; Puvrez, A; Vos, HJ; D"hooge, J; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Research Foundation - Flanders (FWO) Background: Shear wave elastography (SWE) is a promising tool for the non-invasive assessment of myocardial stiffness. It is based on the evaluation of the propagation speed of shear waves by high frame rate echocardiography. These waves can be induced by for instance mitral valve closure (MVC) and the speed at which they travel is related to the instantaneous stiffness of the myocardium. Myocardial stiffness is defined by the local slope of the stress-strain relation and can therefore be altered by both changes in structural properties of the myocardium as well as loading conditions. Purpose: The aim of this study was to investigate how changes in myocardial structural properties as well as loading conditions affect shear wave speed after MVC. Methods: Until now, 8 pigs (weight: 33.6 ± 5.4 kg) were included. The following interventions were performed: 1) preload was reduced by balloon occlusion of the vena cava inferior, 2) afterload was increased by balloon occlusion of descending aorta, 3) preload was increased by intravenous administration of 500 ml of saline and 4) ischemia/reperfusion injury (I/R injury) was induced in the septal wall by balloon occlusion of the LAD for 90 min. with subsequent reperfusion for 40 min. Echocardiographic and left ventricular pressure recordings were simultaneously obtained during each intervention. Left ventricular parasternal long-axis views were acquired with an experimental high frame rate ultrasound scanner (average frame rate: 1279 ± 148 Hz). Shear waves were visualized on tissue acceleration maps by drawing an M-mode line along the interventricular septum. Shear wave propagation speed after MVC was calculated by assessing the slope of the wave pattern on the tissue acceleration map (Figure A). Results: The change in left ventricular end-diastolic pressure (LVEDP) and shear wave speed after MVC between baseline and each intervention are shown in Figure B and C, respectively. Preload reduction resulted in significant lower LVEDP compared to baseline (p < 0.01), while the other loading changes did not have a significant effect. Shear wave speed after MVC significantly increased by afterload and preload increase (p < 0.01). I/R injury resulted in increased shear wave speed (p < 0.01) without significantly altering LVEDP. There was a good positive correlation between the change in LVEDP and the change in shear wave speed induced by loading changes (r = 0.76; p < 0.001) (Figure D). However, the correlation became less strong if data of I/R injury was taken into account as well (r = 0.63; p < 0.001). Conclusion: Our results suggest that SWE is capable to characterize myocardial tissue properties and besides has the potential as a novel method for the estimation of left ventricular filling pressures. However, in the presence of structural changes of the myocardium, care should be taken when estimating filling pressures based on shear wave propagation speed.